Lenalidomide and Rituximab Regimen Combined With Intravitreal Methotrexate Followed by Lenalidomide Maintenance for Primary Vitreoretinal Lymphoma: A Prospective Phase II Study - Zhang, Yan; Zhang, Xiao; Zou, Dongmei; Yin, Jingjing; Zhang, Li; Wang, Xuan; Jia, Congwei; Wang, Wei; Zhao, Danqing; Zhou, Daobin; Zhang, Wei; Zhang, Meifen (Frontiers in Oncology, 2021)
Primary vitreoretinal lymphoma (PVRL) is a rare variant of primary central nervous system (CNS) lymphoma, for which currently there are no optimal treatment options. This prospective single-center study enrolled immunocompetent patients with newly diagnosed PVRL between August 2018 and January 2020. Patients received local and systemic therapies: intravitreal methotrexate (MTX, 400 μg, 0.1 mL) injections for 1 year (total 16 injections) and six cycles of the rituximab (375 mg/m2 on day 1) and lenalidomide (25 mg on day 1–21; R2) regimen. Lenalidomide was maintained for 2 years in patients who had achieved a response. We enrolled 11 patients with a mean age of 58 (range, 48–70) years, of which 10 achieved complete remission at the first evaluation. The median follow-up period was 18.3 (range, 10.6–27.8) months, and the median progression-free survival was 12.7 months. Moreover, a total of eight patients relapsed. The most common adverse event (AE) was neutropenia, which occurred in seven patients (63.6%), followed by grade 3 ocular toxicities, including cataract formation, in six patients (54%). These findings suggest that the R2 regimen combined with intravitreal MTX, followed by lenalidomide maintenance, is a safe option for PVRL with moderate efficacy. This trial is registered with ClinicalTrials.gov (number NCT 03746223).